The selective serotonin reuptake inhibitor sertraline enhances counterregulatory responses to hypoglycemia - Sanders, Nicole M. (2008)
Selective serotonin reuptake inhibitors (SSRIs) are widely prescribed for patients with comorbid diabetes and depression. Clinical case studies in diabetic patients, however, suggest that SSRI therapy may exacerbate hypoglycemia. We hypothesized that SSRIs might increase the risk of hypoglycemia by impairing hormonal counterregulatory responses (CRR). We evaluated the effect of the SSRI sertraline on hormonal CRR to single or recurrent hypoglycemia in nondiabetic rats. Since there are time-dependent effects of SSRIs on serotonin neurotransmission that correspond with therapeutic action, we evaluated the effect of 6- or 20-day sertraline treatment on hypoglycemia CRR. We found that 6-day sertraline (SERT) treatment specifically enhanced the epinephrine response to a single bout of hypoglycemia vs. vehicle (VEH)-treated rats (t = 120: VEH, 2,573 ± 448 vs. SERT, 4,202 ± 545 pg/ml, P < 0.05). In response to recurrent hypoglycemia, VEH-treated rats exhibited the expected impairment in epinephrine secretion (t = 60: 678 ± 73 pg/ml) vs. VEH-treated rats experiencing first-time hypoglycemia (t = 60: 2,081 ± 436 pg/ml, P < 0.01). SERT treatment prevented the impaired epinephrine response in recurrent hypoglycemic rats (t = 60: 1,794 ± 276 pgl/ml). In 20-day SERT-treated rats, epinephrine, norepinephrine, and glucagon CRR were all significantly elevated above VEH-treated controls in response to hypoglycemia. Similarly to 6-day SERT treatment, 20-day SERT treatment rescued the impaired epinephrine response in recurrent hypoglycemic rats. Our data demonstrate that neither 6- nor 20-day sertraline treatment impaired hormonal CRR to hypoglycemia in nondiabetic rats. Instead, sertraline treatment resulted in an enhancement of hypoglycemia CRR and prevented the impaired adrenomedullary response normally observed in recurrent hypoglycemic rats.